Social maturity and thinking flexibility as a basis of student resilience - O. V. Zabrodina; M. I. Ryazanova (Вестник университета)
The article studies mental flexibility and social maturity as a basis of student resilience. Such concepts as social maturity, mental and psychological health, mental flexibility and resilience have been considered. Social maturity, mental flexibility, and psychological health play an important role in adapting to environmental changes. Social maturity and flexibility as important components of a person’s life influence their well-being, satisfaction level, emotional state, help to manage emotions and thoughts, show the ability to cope with stress and learn to accept changes, and find ways to solve problems. They contribute to communication skills development, establishing healthy interpersonal relationships and maintaining positive motivation, as well as help in social and psychological adaptation to new life circumstances, finding the right and effective ways out of any crisis situations and showing curiosity rather than hostility towards the changing aspects of life. Important features of social maturity and thinking flexibility include integration into social and functional processes of life activity, management and self-regulation, and ability to switch from one thought to another without losing the main one. Recommendations for thinking flexibility development have been presented. Such directions in flexible thinking development as practicing open thinking, learning new skills and knowledge, communicating with different people, meditation practicing, reading books, exploring new ideas, and fantasizing have been outlined. The main aspects of resilience have been reflected. Social maturity and thinking flexibility have been considered as a basis of student resilience.